A critical issue: assessing the critical thinking skills and dispositions of undergraduate health science students - Anthony Dissen (Springer, 2023)
Abstract Critical thinking skills and dispositions are significantly important factors that aid in one's ability to understand and solve complex problems. Within the field of higher education, critical thinking skills and dispositions are valued and encouraged but are not always fully developed at the completion of the undergraduate degree experience. Those students who are studying to enter the healthcare field are particularly in need of strong critical thinking skills and dispositions in order to provide patients and communities with effective, evidence-based care in the midst of an ever-increasingly complex environment. What program of study a student selects, and the unique curriculum design of that program, may impact the development of these skills and dispositions during undergraduate study. This quantitative study sought to explore and understand the critical thinking skills and dispositions of undergraduate students enrolled in a BS in Health Science (BSHS) degree program, and how these skills in particular compared to the national student population. During the Spring 2022 academic semester, 140 senior-level BSHS students were given the opportunity to complete the California Critical Thinking Skills Test and the California Critical Thinking Disposition Inventory. Results show less development in critical thinking skills when compared to the national student population, with Numeracy skills being the most poorly developed, and Truth-Seeking being the most inconsistent disposition possessed by the student participants. The implications of these findings, particularly for faculty who teach students planning to enter the healthcare field, are offered, including recommendations for curricular design and modification.